Analysis of the Influence of Maintenance Bank Syariah Indonesia on Mobile Banking Economic Transaction Activities in The Territory of Indonesia - Al-Amin; Nidaan Alfia; Wahyu Nusantara Illahi,S; Fauziah Sukma wati; Hadi Subeno; Husnul Bashir; Refiter Putra; Wira Andespa; Ahmad Ridwan; Elvi Nasriandani; Khairani, Zelfia; Febriani, Winda; Asyari (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
Indonesia Sharia is a financial institution currently trending but has experienced extraordinary maintain in recent times. The purpose of this study is to determine the influence of maintenance Bank Syariah Indonesia on mobile banking economic transaction activities in the territory of Indonesia. This research method is quantitative with descriptive analysis and data collection with questionnaires and the level is the Likert scale of correspondent data on Indonesian Islamic bank customers randomly from various regions of Indonesia affected by a total of 85 people. The results of this study Likewise, the Maintenance of Mobile Banking Services carried out by Bank Syariah Indonesia had a significant and positive effect on Economic Transaction activities in Indonesian territory last week